USTADZ SELEBRITI ABDULLAH GYMNASTIAR (Perspektif Hipersemiotika Yasraf Amir Piliang) - Maskur Maskur (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
The development of popular culture, particularly,in the development of information technology such as as television, mobile phones, and the Internet,  have an impact on the creation of a new reality called hyper-reality. Media,in this case,is able to reconstruct a new reality through the sophisticated technology. The construction of this medium also penetratesthe religious area. This can be seen in the figure of Abdullah Gymnastiar (Aa Gym). Through the medium of information, Aa Gym is not only seen as a religious teacher who offers a depth of spirituality but also as a celebrity through the image formed. This paper aims to identify and describe the phenomenon of celebrity cleric/ ustadzAbdullah Gymnastiar in popular culture, using hyper-semioticsapproachof Yasraf Amir Piliang. This paper attempts to explain the new realityof diversity of Abdullah Gymnastiar. Through the hyper-semioticsapproach, religious hyper-reality form can be described scientifically.